2017
DOI: 10.1080/00397911.2017.1365906
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of several types of 2,8-dioxabicyclo[3.3.1]nonanes using amberlyst-15 as an efficient recyclable heterogeneous catalyst

Abstract: Contents:1. General experimental procedure for synthesis of compounds 2-6 and S2their characterization data 2. Copies of 1 H NMR and 13 C NMR spectra S9-S24 3. References S25 S2 2. General Experimental Procedure for Synthesis of Compounds 2-6 and Their Characterization Data General Information Melting points were recorded on a Köfler block. IR spectra were recorded on a Perkin Elmer FT-IR spectrophotometer (Spectrum BX II) in KBr pellets. 1 H and 13 C NMR spectra were recorded in CDCl 3 on a Bruker AV-300 (300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Our recent studies on amberlyst‐15 catalysed condensation of 2‐hydroxychalcones with a number of carbon nucleophiles under aerial condition showed that in cases of use of some carbon nucleophiles ( viz ., dimedone, 4‐hydroxycoumarin, 2‐hydroxy‐1,4‐napthoquinone, 1‐naphthol, 2‐naphthol and 4‐hydroxy‐6‐methyl‐2 H ‐pyran‐2‐one) 2,8‐dioxabicyclo‐[3.3.1]nonanes were formed,, while use of others ( viz ., indan‐1,3‐dione, cyclopentan‐1,3‐dione and 1,3‐dimethylbarbituric acid) gave 4 or its analogues through a different path with the occurrence of an aerial oxidation in the last step . A careful examination of the proposed mechanisms ( Scheme ),, suggests that the possible reason for this difference may be the different enolization ability of the attached moiety in the intermediates coming from the nucleophile.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies on amberlyst‐15 catalysed condensation of 2‐hydroxychalcones with a number of carbon nucleophiles under aerial condition showed that in cases of use of some carbon nucleophiles ( viz ., dimedone, 4‐hydroxycoumarin, 2‐hydroxy‐1,4‐napthoquinone, 1‐naphthol, 2‐naphthol and 4‐hydroxy‐6‐methyl‐2 H ‐pyran‐2‐one) 2,8‐dioxabicyclo‐[3.3.1]nonanes were formed,, while use of others ( viz ., indan‐1,3‐dione, cyclopentan‐1,3‐dione and 1,3‐dimethylbarbituric acid) gave 4 or its analogues through a different path with the occurrence of an aerial oxidation in the last step . A careful examination of the proposed mechanisms ( Scheme ),, suggests that the possible reason for this difference may be the different enolization ability of the attached moiety in the intermediates coming from the nucleophile.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a large number of synthetic procedures have been reported in a brief period of time (2013–2019) to achieve the synthesis of A-type PAC analogues through chalcones. In all of these studies, the optimization of the experimental conditions for the coupling reaction between a given chalcone and the π-nucleophile has carefully been performed, selecting the proper set of catalyst, solvent, and temperature for each individual reaction (Table ).…”
Section: Synthesis Of A-type Pac Analoguesmentioning
confidence: 99%
“…The main differences between all of these procedures lie in the electrophilic activation of α,β-unsaturated ketone and the reaction solvent used. In this sense, the activation has been performed by Lewis acid, ,, Brønsted acid, ,,,, organobases, and also without any catalyst. , It seemed that the reaction started with a 1,4-conjugate addition between 2-hydroxychalcone ( 31 ) and the corresponding π nucleophile ( 35 ), affording the key intermediate (±)- 36 , which quickly evolved to the target bicyclic compound (±)- 38 through a double intramolecular cyclization (Scheme ). ,, …”
Section: Synthesis Of A-type Pac Analoguesmentioning
confidence: 99%